2011
DOI: 10.1074/jbc.m110.208595
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Human Golgi-resident Glutaminyl Cyclase and Its Complexes with Inhibitors Reveal a Large Loop Movement upon Inhibitor Binding

Abstract: Aberrant pyroglutamate formation at the N terminus of certain peptides and proteins, catalyzed by glutaminyl cyclases (QCs), is linked to some pathological conditions, such as Alzheimer disease. Recently, a glutaminyl cyclase (QC) inhibitor, PBD150, was shown to be able to reduce the deposition of pyroglutamate-modified amyloid-␤ peptides in brain of transgenic mouse models of Alzheimer disease, leading to a significant improvement of learning and memory in those transgenic animals. Here, we report the 1.05-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…Our findings rationalize the elevated levels of serum lipase found in patients undergoing DPP4 inhibitor based therapies 28, 29 , although these reports are in disagreement with other findings 30, 31 . While it is logical and expected to find scaffolds that are congruent to trypsin and DPP4 active sites in lipases based on the current results and our previous findings 22 , we also show the presence of the serine catalytic triad in close proximity to the active site residues of proteins which have a completely different enzymatic mechanism (for example, in glutaminyl cyclase which is a transferase 32 ). This corroborates the current belief that convergent evolution occurs more frequently than previously believed 33 .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings rationalize the elevated levels of serum lipase found in patients undergoing DPP4 inhibitor based therapies 28, 29 , although these reports are in disagreement with other findings 30, 31 . While it is logical and expected to find scaffolds that are congruent to trypsin and DPP4 active sites in lipases based on the current results and our previous findings 22 , we also show the presence of the serine catalytic triad in close proximity to the active site residues of proteins which have a completely different enzymatic mechanism (for example, in glutaminyl cyclase which is a transferase 32 ). This corroborates the current belief that convergent evolution occurs more frequently than previously believed 33 .…”
Section: Introductionsupporting
confidence: 77%
“…However, our methodology also detects other proteins, often with a completely different enzymatic mechanism from hydrolases. A glutaminyl cyclase (PDBid:3PB4 32 ), a transferase, has a significantly congruent domain with Motif1 (lesser congruence with Motif2, as indicated by the RMSD) ( Table 1). Figure 3 shows the proximity of the promiscuous scaffold to the active site of the cyclase, and also the congruence of the scaffold to Motif1.…”
Section: Resultsmentioning
confidence: 99%
“…The 15 N HSQC performed on the 70 µM 15 N, 13 C 6xmut hQPCT is reported in Figure 3C. NMR was also used to demonstrate the binding of the ligand PBD150, a known inhibitor of wild type hQPCT [13] that we have found to inhibit also the activity of the 2xmut (see above). A titration of the 2xmut 15 N labeled protein with increasing amounts of this inhibitor was performed.…”
Section: Resultsmentioning
confidence: 95%
“…The mapping is possible whenever the following conditions are met: i ) a structure of the protein and ii ) the assignment of the 1 H- 15 N HSQC spectrum are available [8], [9], [10], [11]. While the first condition has been achieved by X-ray crystal structure determinations (PDB id: 2ZED, 3SI1, 2AFM, 3PBB), [4], [5], [12], [13] no NMR assignment exists yet for hQPCT, nor 1 H- 15 N HSQC spectra have been reported. Given the size of the protein, this might be accomplished via triple resonance NMR experiments that require 15 N, 13 C and partial 2 H enrichment on protein forms with a solubility of hundreds of µM [14].…”
Section: Introductionmentioning
confidence: 99%
“…These two QCs share ∼ 45 % sequence identity and similar catalytic characteristics [7]. Previous studies indicated that the enzymatic activity of isoQC is ∼ 3-fold weaker on several synthetic substrates than the activity of sQC [8]. A tissue distribution analysis revealed that the expression of isoQC is ubiquitous [7], whereas sQC expression is higher in neuronal tissues and in several peripheral blood lymphocytes [1].…”
Section: Introductionmentioning
confidence: 99%